Impact of information and communication technology on organization - Sutekno, Ahmadbelon (UNIMAS, 2003)
The objective of this study is to determine the impact of ICT enablers that are organization chooses to have [with the influence of existing internal and external environment of the organization (mediating factors)] on the organization as a whole